The Efficacy of Vitamin D Supplementation to Reduce Urticaria: Systematic Review - Devi, Jean Budi Pratista; Rohmawati, Indah (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
Urticaria is a condition of skin disorders. Based on the duration of symptoms, chronic urticaria occurs > 6 weeks. Chronic urticaria is caused by endogenous factors unrelated to an external physical stimuli. Vitamin D is an immunoregulatory hormone that activates innate and adaptive immune responses. A literature search was conducted in PubMed, ScienceDirect, SpringerLink, and ProQuest with a publication year limit of 2011–2023. The keywords used were "vitamin D deficiency and urticaria" and "vitamin D and urticaria". The present review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020. This review included four case reports from 2247 articles. All cases showed a low risk of bias. Two studies found were case-control studies that met the inclusion criteria. The Johanna Briggs Institute checklist was used to assess the risk of bias. The data were presented descriptively. Chronic spontaneous urticaria (CSU) is more common in women than men.. Patients CSU had < 30 ug/ml vitamin D level and experienced reduced urticarial symptoms after receiving vitamin D (p < 0, 001). Vitamin D2 supplement at 20,000 IU for 6 weeks alleviated urticarial symptoms in patients CSU. Alongside vitamin D, antihistamines, and corticosteroid were also recommended as a comination therapy, leading to a better clinical outcome. Vitamin D supplementation reduces symptoms in patients with CSU. A combination therapy with antihistamines and corticosteroid should be considered in clinical practice.